Comorbidity between ADHD and epilepsy: a narrative review - Spagnoli, Carlotta; Ioppi, Anna; Di Santo, Federica; Rollo, Dolores; Pisani, Francesco (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Epilepsy is a common neurological disease, posing unique management challenges and opportunities in children, especially if neurodevelopmental disorder(s) coexist. The association between epilepsy and attention deficit hyperactivity disorder (ADHD) is well known. However, knowledge gaps persist, and dedicated clinical and experimental studies are not numerous. Methods: With this narrative literature review, we wish to describe the association between ADHD and epilepsy in children in terms of epidemiology, clinical presentation, potential pathophysiological bases, diagnostic challenges, therapies, and outcomes. Pubmed and Google Scholar were interrogated with the search terms “ADHD” OR “attention deficit and hyperactivity disorder” AND “epilepsy”. We only included papers written in English and focusing on the pediatric age (0-18 years). Additional papers were retrieved by manually searching the reference lists of selected papers. No study period limitation was applied. The search ended on 24th February 2024. Results: ADHD in children with epilepsy is common, most often with inattentive presentation and similarly affects boys and girls. It is likely linked to epilepsy by a bidirectional association based on shared neurobiological factors, of genetic and environmental origin, only marginally understood. It significantly impacts prognosis, being associated with lower academic performances and increased risk of psychiatric comorbidities. However, comorbid ADHD is often under-recognized in children with epilepsy, with inattention being attributed to epilepsy or to antiseizure medications. It is also under-treated, due to an overestimation of the risk of lowering the seizure threshold with psychostimulants. Conclusions: Further research and increased awareness are warranted to improve management and outcome.